(3bhGYO GdCMcGes - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3eMeO HGbQ Hf YHO GdHGbj GdGKfi YTQjs)
(3ChdgG (B:s
(3cJGH GdfcGM hajg CHhGH(B: (3GdChd aj GdebOeGJ hgj(B: (3SHYI eHGMK(B: (3GdfcGM eSJMH, hjJCcO aj GdbGOQ eY TOI WdHg(B. (3hbO jLH EPG NTj GdhbhY aj GdRfG, ShGA GdQLd hGdeQCI(B. (3hGdCbQH(B: (3Cfg CaVd ef GdJNdj ddYHGOI def de JJb faSg Edjg(B. (3hjfHZj(B: (3Cf jJNjQ GdhdhO, GdHcQ, GdYajaI, s
(3BNQgG (B:s
(3hbO hVYJ dc cJHG eJYOOI aj Pdc cdg(B. (3gPG eG jQLY Edjc(B. (3hCeG eG jQLY Edj hjYhO faYg Ydj(B: (3aCf JJYgOfj HGdJQMe aj HYV GdChbGJ (B.... (3gPg hUjJj Edjc, hGddg NdjaJj Ydjcs
(3HYOgG HebOGQ hQbJjf QSGdI dHgGA GdOjf GdYGedj aj CUhd GdOjf GdNeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B2/227s
(3EjVGM Gdecfhf (B2\242s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis